Bronchial wall thickening is associated with severity of chronic rhinosinusitis. (August 2020) - Majima, Suguru; Wakahara, Keiko; Nishio, Tomoko; Nishio, Naoki; Teranishi, Masaaki; Iwano, Shingo; Hirakawa, Akihiro; Hashimoto, Naozumi; Sone, Michihiko; Hasegawa, Yoshinori
Abstract: Background: Though the relationship between chronic rhinosinusitis (CRS) and lower airway diseases is well recognized, the impact of CRS on bronchial wall structure has not been elucidated. Here, we evaluated the bronchial wall structure of CRS patients with or without diagnosed airway diseases by three-dimensional computed tomography (3D-CT). Methods: Subjects who underwent both chest CT and sinus CT within a year were recruited from consecutive medical records. CRS was defined as a Lund-Mackay score (LMS) of over 5 points. Airway dimensions were measured using validated software. Standard blood tests and pulmonary function tests were performed, and their correlation with airway thickness was examined. Results: One-hundred-seventy-two patients were recruited (93 CRS subjects and 79 non-CRS subjects). The bronchial walls of CRS subjects were significantly thicker than those of non-CRS subjects. CRS and asthma were related to bronchial wall thickening by multivariate linear regression analysis adjusted for age, smoking status, and chest symptoms. In addition, LMS was significantly correlated with bronchial wall thickening. Conclusion: Airway walls in CRS subjects were thicker than those in non-CRS subjects and associated with the severity of CRS. These data indicate strong relationship between upper and lower airways regardless of chest symptoms or diagnosed airway diseases. Highlights: Chronic rhinosinusitis (CRS) patients have thicker airway walls regardless of chest symptoms or diagnosed airway diseases. Severity of CRS evaluated by Lund-Mackay score (LMS) is positively correlated with airway dimensions. Strong relationship between upper and lower airway consistent with the concept of "United airway disease". Quantitative CT analysis of airway dimensions may also be a useful technique for assessing subclinical inflammation.